Shut up, this is serious - Ixta, Carolina (Quill Tree Books, an imprint of HarperCollins Publishers, 2024)
Belen Dolores Itzel del Toro wants the normal stuff: to experience love or maybe have a boyfriend or at least just lose her virginity. But nothing is normal in East Oakland. Her father left her family. She's at risk of not graduating. And Leti, her super-Catholic, nerdy-ass best friend, is pregnant--by the boyfriend she hasn't told her parents about because he's Black and her parents are racist.